Polyethylenimine‐modified curcumin‐loaded mesoporus silica nanoparticle (MCM‐41) induces cell death in MCF‐7 cell line. Issue 1 (4th November 2016) - Harini, Lakshminarasimhan; Karthikeyan, Bose; Srivastava, Sweta; Suresh, Srinag Bangalore; Ross, Cecil; Gnanakumar, Georgepeter; Rajagopal, Srinivasan; Sundar, Krishnan; Kathiresan, Thandavarayan
Abstract : Breast cancer accounts for the first highest mortality rate in India and second in world. Though current treatment strategies are effectively killing cancer cells, they also end in causing severe side effects and drug resistance. Curcumin is a nutraceutical with multipotent activity but its insolubility in water limits its therapeutic potential as an anti‐cancer drug. The hydrophilicity of curcumin could be increased by nanoformulation or changing its functional groups. In this study, curcumin is loaded on mesoporous silica nanoparticle and its anti‐cancer activity is elucidated with MCF‐7 cell death. Structural characteristics of Mobil Composition of Matter ‐ 41(MCM‐41) as determined by high‐resolution transmission electron microscopy (HR‐TEM) shows that MCM‐41 size ranges from 100 to 200 nm diameters with pore size 2–10 nm for drug adsorption. The authors found 80–90% of curcumin is loaded on MCM‐41 and curcumin is released efficiently at pH 3.0. The 50 µM curcumin‐loaded MCM‐41 induced 50% mortality of MCF‐7 cells. Altogether, their results suggested that increased curcumin loading and sustained release from MCM‐41 effectively decreased cell survival of MCF‐7 cells in vitro.